Validation of the Hong Kong Oral Health Literacy Assessment Task for Paediatric Dentistry (HKOHLAT‐P). Issue 5 (24th January 2013) - Wong, Hai Ming; Bridges, Susan M.; Yiu, Cynthia K. Y.; McGrath, Colman P. J.; Au, Terry K.; Parthasarathy, Divya S.
<x xml:space="preserve">Abstract</x> Background Oral health literacy is a newly emerging field with considerable research potential. Aim To validate an original instrument, the Hong Kong Oral Health Literacy Assessment Task (HKOHLAT‐P) for paediatric dentistry. Design A convenient sample of 200 child/parent dyads attending a dental hospital in Hong Kong was selected. Convergent validity was tested by examining the association of HKOHLAT‐P scores with those derived from the Test of Functional Health Literacy in Dentistry (TOFHLiD) and Hong Kong Rapid Estimate of Adult Literacy in Dentistry (HKREALD‐30). The predictive validity of HKOHLAT‐P was determined by testing the association between HKOHLAT‐P and children's caries experience (dmft) and the Chinese Early Childhood Oral Health Impact Scale (ECOHIS). The test‐retest reliability and internal consistency of HKOHLAT‐P were also evaluated. Results HKOHLAT‐P was positively correlated with TOFHLiD and HKREALD‐30 (P < 0.01), and was negatively correlated with children's dmft and ECOHIS. In the regression model, HKOHLAT‐P was associated with TOFHLiD, HKEALD‐30, children's dmft, and ECOHIS (P < 0.05) after controlling for participants' demographic characteristics. The intra‐class correlation coefficient of HKOHLAT‐P was 0.63 and the Cronbach's α was 0.71. Conclusion Initial testing of HKOHLAT‐P suggested that it is a valid and reliable instrument.